Protection of Human Rights: Participation of European International Organisations in Regulating the Functioning of Artificial Intelligence (AI) Technologies - Beskorovaynaya, Svetlana; Karimova, Dilafruz; Akhyadov, Elman; Kolganov, Sergei; Mamazova, Zarifa; Aleshkov, Alexey (Jurnal Cita Hukum, 2025)
The authors of this article explore the potential solutions to the issue of threats to human rights arising from the development of artificial intelligence (AI) technologies. The research problem is examined within the framework of international law, focusing particularly on adopting relevant legal instruments at the global or supranational level, especially within the European Union (EU) and the Council of Europe. This study employs a qualitative research method, using a literature-based and legal approach to review and analyse existing regulations systematically, scholarly discussions, and legislative initiatives. Additionally, the case-study method is utilized to examine key legislative instruments adopted within the EU that regulate the use of AI in the context of human rights protection. Through this approach, the article highlights the similarities and differences between the compared legal acts, particularly concerning the threats posed by AI technologies and their projected future significance. The findings indicate that the analysed legal instruments are vital for safeguarding individuals' rights against risks emerging from the rapid development of AI. Furthermore, the authors conclude that the effective and practical implementation of these regulations at the national level in EU member states will play a critical role in shaping similar legal frameworks within the broader sphere of international law.